2015
DOI: 10.1073/pnas.1420811112
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 has a TP53-dependent dual role in regulating breast cancer cell growth

Abstract: Breast cancer is a leading cause of cancer-related death, and it is important to understand pathways that drive the disease to devise effective therapeutic strategies. Our results show that Toll-like receptor 4 (TLR4) drives breast cancer cell growth differentially based on the presence of TP53, a tumor suppressor. TP53 is mutationally inactivated in most types of cancer and is mutated in 30-50% of diagnosed breast tumors. We demonstrate that TLR4 activation inhibits growth of TP53 wild-type cells, but promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 25 publications
2
67
2
Order By: Relevance
“…The experiment was repeated three times. NC, negative control; TLR4, toll-like receptor 4; RT-qPCR, reverse transcription quantitative polymerase chain reaction; CDK4, Cyclin-dependent kinase4 antibody; c-FLIP, FLICE-inhibitoryprotein cancer could be induced on disruption of TLR4 gene function in some breast tumors (Haricharan & Brown, 2015). A high expression of TLR4 has been observed in human breast cancer tissues, compared to its minimal expression in normal breast tissues (Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was repeated three times. NC, negative control; TLR4, toll-like receptor 4; RT-qPCR, reverse transcription quantitative polymerase chain reaction; CDK4, Cyclin-dependent kinase4 antibody; c-FLIP, FLICE-inhibitoryprotein cancer could be induced on disruption of TLR4 gene function in some breast tumors (Haricharan & Brown, 2015). A high expression of TLR4 has been observed in human breast cancer tissues, compared to its minimal expression in normal breast tissues (Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines were obtained from American Type Culture Collection (ATCC, 2015) and maintained and validated as previously reported (44) Mycoplasma tests were performed on parent cell lines and stable cell lines every 6 months (latest test: 05/17) with the Lonza Mycoalert Plus kit (cat# LT07-710) as per manufacturer’s instructions. Cell lines were discarded at <25 passages, and fresh vials were thawed out.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection and validation of CRISPR and shRNA plasmids was conducted as previously 23 . Transient transfection with siRNA against CHEK2 was conducted as previously(44), and siRNA pools were purchased from Sigma Aldrich. Stable cell lines were established in the presence of specified antibiotics at recommended concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, TLR4 appears to be a promising target for immune-based therapeutic options and is the focus of many drugs currently in development. However, a recent study demonstrated that TLR4 activation promotes cell growth in p53-mutant breast cancers, but inhibits cell growth in p53 wildtype breast cancers (129). The differential effects appear to be mediated by tumor cell cytokine secretions upon TLR4 activation.…”
Section: Targeting Pathways That Are Critical For Growth Of P53-mutanmentioning
confidence: 99%